Author Response: Association of Sleep, Neuropsychological Performance, and Gray Matter Volume With Glymphatic Function in Community-Dwelling Older Adults. (23rd August 2022) - Siow, Tiing Yee; Toh, Cheng Hong; Hsu, Jung-Lung; Liu, Geng-Hao; Lee, Shwu-Hua; Chen, Ning-Hung; Fu, Changjui James; Castillo, Mauricio; Fang, Ji-Tseng
Abstract : We appreciate Dr. Kawada's constructive comments on our statistical methods. 1 We evaluated the univariate associations between diffusion tensor imaging-analysis along the perivascular space (DTI-ALPS) and the demographic/clinical variables and found that only age and pulse rate had significant association with DTI-ALPS ( p = 0.001 and p = 0.4, respectively).